An Evaluation of Partially Edentulous Patients Visiting Kantipur Dental College: A Hospital-Based Study - Shrestha, B; Shrestha, S; Sah, MP; Karmacharya, R; Miya, N; Ghimire, B (Journal of Nepalese Prosthodontic Society, 2023)
Objective: To evaluate data with regards to the current prevalence of various Kennedy’s classes of edentulism and their association with age. Material and Methods: A total of 157 patients were selected, and the prevalence of partial edentulism among the selected patient was recorded. Patients were grouped into three age groups. Kennedy’s classification was used to determine the pattern of partially edentulous arches. Data was analyzed using the Statistical Package for the Social Sciences version 20.0 for Windows. Results: The results showed that the occurrence of Kennedy Class III partial edentulism was 44.9% in the maxillary arch and 67.4% in the mandibular arch, followed by Class II in both the maxillary and mandibular arch with an average of 15.9% in the maxillary arch and 4.9% in the mandibular arch. Based on these results, Kennedy’s Class III was the most prevalent partially edentulous pattern 57.8% among the maxillary and the mandibular arch. Conclusions: Among selected patients, the prevalence of Class I and II was predominant among elderly population of > 50 years, whereas Class III was present among all ages.